Feudal America : Elements of the Middle Ages in Contemporary Society - Shlapentokh, Vladimir (Book collections on Project MUSE., 2011)
"Uses a feudal model to analyze contemporary American society, comparing its essential characteristics to those of medieval European societies"--Provided by publisher.